Does employee ownership improve performance? - Douglas Kruse (IZA World of Labor, 2016)
Employee ownership has attracted growing attention for its potential to improve economic outcomes for companies, workers, and the economy in general, and help reduce inequality. Over 100 studies across many countries indicate that employee ownership is generally linked to better productivity, pay, job stability, and firm survival—though the effects are dispersed and causation is difficult to firmly establish. Free-riding often appears to be overcome by worker co-monitoring and reciprocity. Financial risk is an important concern but is generally minimized by higher pay and job stability among employee owners.
Keywords: J54; J33; M52; M54; P13; J32; 330; employee ownership; profit sharing; economic performance; economic stability; unemployment; economic inequality